Short Communication: The use of lactose-astaxanthin to maintain the quality of green junglefowl frozen semen (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Bebas W, Agustina KK. 2022. Short Communication: The use of lactose-astaxanthin to maintain the quality of green junglefowl frozen semen.Biodiversitas 23: 5759-5764. The Green Junglefowl is Indonesian germplasm that is at risk of population decline. Therefore, efforts are needed to protect its existence and survival. Cryopreservation of spermatozoa in the form of frozen semen is required to preserve this germplasm. This research aims to determine the effect of lactose-astaxanthin in preventing DNA fragmentation and intact plasma membrane of Green Junglefowl spermatozoa during the freezing process. A completely randomized design with a 2x4 factorial pattern, including two treatment groups and four dimethylsulfoxide (DMSO) concentration factors, was used. The treatment groups are T1 and T2, consisting of egg yolk phosphate diluent and egg yolk phosphate diluent added with a combination of 0.6% lactose-0.004% astaxanthin, respectively. The four DMSO concentration factors were 4%, 6%, 8%, and 10% respectively. Subsequently, each treatment was repeated four times. The DNA fragmentation and intact plasma membrane of spermatozoa were observed, and the data obtained afterward were analyzed for variance, followed by the Ducan test. The results showed that the addition of 0.6% lactose-0.004% astaxanthin with 6% DMSO had a significantly better effect (P